Late IIUM rector Kamal Hassan shaped varsity physically and spiritually - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2023)
I MET the late Professor Muhammad Kamal Hassan, who died on Feb 23, more than a decade ago as vice-chancellor or rector of our universities.